Social Design Enterprises in Thailand: Potentials and Challenges - Natakun, Boonanan; Teerapong, Khemmiga (Journal of Architectural/Planning Research and Studies (JARS), 2014)
Design professions have generally connected to the commercial world rather than being a socially conscious practice. This paper aims to explore ideas and operations of social design practices that combine the value of social responsibility with designers’ day-to-day practices. This study examines social design enterprises in the field of advertising and architectural design in Thailand: Choojai Creative for Good(s) and Openspace. Although potential clients, products, and production time required by these two design businesses are relatively different in nature, they share similar design philosophy and process which is participatory applied at the beginning of the project until the production process. Thus, these professional social design groups are able to embed social responsibility values into their design projects which are illustrative of a social model of design enterprise that serves specific groups of people and Thai society more broadly. In-depth interviews with co-founders, designers and partners/ clients of the selected social design firms were employed to explore ideas, aspirations and needs. Moreover, to examine values embedded in their social design, discourse analysis of media release and reviews of their successful design projects were also undertaken. Findings have shown that social design firms have emerged and become part of Thai design industry when designers and architects can balance between idealism with pragmatic management of limited resources. The discussion has illustrated potential and challenges of social design firms as a business model by concluding that designers’ past reputations, social networks and broader community engagement through media releases are essential for social design firms to succeed their social design projects and to survive as business firms in the real market.